Coordinated Dynamic Gene Expression Changes in the Central Nucleus of the Amygdala During Alcohol Withdrawal. (24th July 2012) - Freeman, Kate; Staehle, Mary M.; Vadigepalli, Rajanikanth; Gonye, Gregory E.; Ogunnaike, Babatunde A.; Hoek, Jan B.; Schwaber, James S.
Abstract : Background: Chronic alcohol use causes widespread changes in the cellular biology of the amygdala's central nucleus (CeA), a GABAergic center that integrates autonomic physiology with the emotional aspects of motivation and learning. While alcohol‐induced neurochemical changes play a role in dependence and drinking behavior, little is known about the CeA's dynamic changes during withdrawal, a period of emotional and physiologic disturbance. Methods: We used a qRT‐PCR platform to measure 139 transcripts in 92 rat CeA samples from control ( N = 33), chronically alcohol exposed ( N = 26), and withdrawn rats ( t = 4, 8, 18, 32, and 48 hours; N = 5, 10, 7, 6, 5). This focused transcript set allowed us to identify significant dynamic expression patterns during the first 48 hours of withdrawal and propose potential regulatory mechanisms. Results: Chronic alcohol exposure causes a limited number of small magnitude expression changes. In contrast, withdrawal results in a greater number of large changes within 4 hours of removal of the alcohol diet. Sixty‐five of the 139 measured transcripts (47%) showed differential regulation during withdrawal. Over the 48‐hour period, dynamic changes in the expression of γ‐aminobutyric acid type A (GABAA ), ionotropic glutamate and neuropeptide system–related G‐protein‐coupled receptor subunits, and the Ras/Raf signaling pathway were seen as well as downstream transcription factors (TFs) and epigenetic regulators. Four temporally correlated gene clusters were identified with shared functional roles including NMDA receptors, MAPKKK and chemokine signaling cascades, and mediators of long‐term potentiation, among others. Cluster promoter regions shared overrepresented binding sites for multiple TFs including Cebp, Usf‐1, Smad3, Ap‐2, and c‐Ets, suggesting a potential regulatory role. Conclusions: During alcohol withdrawal, the CeA experiences rapid changes in mRNA expression of these functionally related transcripts that were not predicted by measurement during chronic exposure. This study provides new insight into dynamic expression changes during alcohol withdrawal and suggests novel regulatory relationships that potentially impact the aspects of emotional modulation.